Survivin expression in colorectal: real time polymerase chain reaction and correlation with clinicopathological features - Said Saleh; King, Alfred Yin Lam; Yik, Hong Ho (Penerbit Universiti Kebangsaan Malaysia, 2014)
Colorectal cancer develops in a multi-step process and is associated with genetic alterations. Blocking apoptosis is a key factor to unlimited cell proliferation and immortalization. Survivin expression inhibits the programmed cell death process, apoptosis. This molecule could play a potential role in cancer development. Survivin is an attractive target for clinical trials to develop cancer treatment. RNA was prepared from colorectal tumor and adjacent non-tumor tissues and then transcribed to complementary DNA. Human survivin mRNA levels were quantitatively measured by real time polymerase chain reaction (PCR) in tumor and adjacent non-tumor tissues. Expression levels of survivin mRNA in adenocarcinomas were significantly higher than in non-tumor mucosa (p < 0.0001). The expressions of survivin mRNA in adenocarcinomas were related to the degree of differentiation (survivin; p=0.034). No difference was found with other clinicopathological features. These findings indicate survivin role in colorectal carcinogenesis. Survivin could be used as a potential diagnostic and prognostic marker in colorectal cancer. Successful inhibition of this molecule could lead to the development of a new drug for cancer therapy.